Introduction to global sustainable management - Combe, Colin (Los Angeles : SAGE, 2022)
At a time when the effects of climate change are becoming all too real for ordinary citizens around the world, this essential textbook offers insight into how managers can shape and influence the development of sustainability practices as a means of tackling some of the most pressing social, economic, and environmental challenges. Featuring a distinctly international array case studies and examples, as well as learning outcomes, definitions, questions, tasks and further reading, Introduction to Global Sustainable Management provides readers with a valuable understanding of how sustainable management practices can be implemented in different industry sectors across the globe. Suitable for upper-level undergraduate and postgraduate students of sustainable management-related courses. A Tutor's Guide, PowerPoint slides and selected SAGE Business Cases are available to instructors via the companion website. Colin Combe is a senior lecturer in strategic management at Glasgow Caledonian University, UK.
Global Sustainable Management: Introduction; Global Sustainable Management Theory; Strategic Thinking and Global Sustainability Management; Triple Bottom Line, Accountability and Transparency; Sustainability Skills and Competences; Sustainability Marketing; Sustainable Operations and Supply Chain Management; Ethics and Corporate Social Responsibility; Sustainability Culture; Sustainability Leadership
Includes bibliographical references (pages 271-285) and index.
Keywords: Business enterprises -- Environmental aspects; Industrial management -- Environmental aspects; Social responsibility of business; Sustainable development; Strategic planning